Crystallization of nordstrandite in ethylene glycol water solutions: electron microscopic studies - Pereira Antunes, Maria Lucia [UNESP]; Santos, Helena Souza; Santos, Persio Souza (Versita, 2009)
The present work shows the growth of nordstrandile microcrystals observed by transmission and scanning electron microscopy. Nordstrandite was synthesised from non-crystalline aluminium hydroxide reacted in 20% ethylene glycol/water solution, at room temperature. This material was characterized by TEM, SEM, SAED, XRD and EDS/TEM, during six month and revealed the formation and growth of nordstrandite. Fibrillar pseudoboehmite is the only aluminium hydroxide which could be identified during the first two weeks. The nuclei grow, from complete dissolution/recrystallization of pseudoboehmite fibrils, into platy rectangular microscrystals of nordstrandite. Some tabular microcrystals recrystallise, forming after six months only the mufti-point nordstrandite stars. This electron-optical study suggest that the star shape results from the overlapping of rectangular plates, and pseudoboehmite fibrils act as the precursor of nordstrandite crystallisation in ethylene glycol/water solution.
Keywords: Aluminium hydroxide; Crystal growth; Electron microscopy; Nordstrandite